Decolonizing History Curricula Across Canada: Recommendations for (Re)design - Karn, Sara; Llewellyn, Kristina R.; Clark, Penney (Canadian Journal of Education / Revue canadienne de l'éducation, 2024)
This study explores how K–12 history curricula across Canada currently address—and may better address in future—decolonizing imperatives. Following a consideration of the limitations and strengths of curricula in this regard, the article identifies five recommendations for (re)designing history and social studies curricula with decolonizing goals in mind: (1) challenge hegemonic narratives, (2) value Indigenous ways of knowing and being, (3) reflect on privilege and positionality, (4) engage in the ethical dimension, and (5) focus on the future. Each recommendation is informed by the empirical study of curricula, and positioned in relation to scholarly conversations about the responsibility of history education that seeks to respond to calls for decolonization.